Rekonseptualisasi Technology Acceptance Model (Tam) Dalam Pedagogi Bahasa Inggris Berbasis Nilai Islam: Studi Fenomenologi Terhadap Guru di Pesantren Darul Falah - Romzatul Widad; Novi Darmayanti; Ah. Zakki Fuad (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The integration of technology in English language learning within pesantren often faces challenges in balancing digital developments with the preservation of Islamic values. This study aims to develop the traditional Technology Acceptance Model (TAM), which focuses on Perceived Usefulness and Perceived Ease of Use, by incorporating Islamic values as an important factor in technology acceptance. Using a qualitative phenomenological approach, data were collected through in-depth interviews with English teachers in the pesantren environment. The findings show that technology acceptance among teachers at Pesantren Darul Falah is influenced not only by the usefulness and ease of technology but also by moral and religious considerations, referred to as Islamic Perceived Appropriateness. The reconceptualization of TAM in this study results in a new model that places Islamic values, digital ethics, and public benefit as the main foundations for technology adoption. The findings highlight the importance of developing digital learning media that are aligned with the cultural and religious characteristics of Islamic educational institutions.